Christianity in Persia and the status of non-muslims in Iran - Van Gorder, A. Christian (Lanham : Lexington Books, 2010)
Writing on an often overlooked section of contemporary Persian culture, A. Christian Van Gorder provides a comprehensive and readable introduction to the experience of Christians and other non-Muslims in Iran throughout history and into the present day. Van Gorder gives a fascinating account of the history of Christianity in Persia. By debunking the common misconceptions and stereotypes driven by recent political events and the media, he shows the current relationship that Muslim majority in Iran has taken toward people of other faiths.
Introducing the land of Persia and early Persian history -- Early Persian religions, Judaism, and Christianity, before Islam -- The rise of Islam and the role of non-muslims in Persian Islam -- Types of Islam in Persia and Iran -- Modern protestant missionary efforts in Persia -- Non-Muslims and the Islamic revolution of 1979 -- Contemporary Christianity in Iran -- Persecution of protestants in modern Iran -- Conclusion : the future of Christian and Muslim relations in Iran -- Appendix I: international organizations confronting religious persecution (2009) -- Appendix II: statements from the universal Islamic declaration on human rights -- Appendix III: timeline of Persian history -- Appendix IV: chronological list of rulers in Iran -- Appendix V: ethnic and religious groups in Iran (1999) -- Appendix VI: non-Muslim religious minorities -- Glossary of Arabic and Persian terms and names.
Includes bibliographical references (p. 305-320)and index.
Description based on print version record.
Keywords: Christianity -- Iran; Islam -- Iran; Iran -- Religion; Christianity; Iran; Islam; Religion; RELIGION -- Christianity -- History; Electronic books